Fundamentals of Provincial Governance in Nepal’s Federalism - Subedi, Girdhari (Journal of Political Science, 2020)
The objective of this article is to answer the state of provincial states and the challenges faced by them, and to show the constitutional provisions for coordination, cooperation and coexistence of inter-provincial relations of Nepalese new federal set up. The provincial governments are facing lots of challenge including resource, proper policies, devolution of power and bureaucratic accountability and lack of intra-provincial coordination. The constitution stands on tri-pillar theory (cooperation, coexistence and coordination) to operate the holding together federalism in Nepal. In this article, an empirical facts and field observation of Gandaki Province have been analyzed. The writer argues that other provinces throughout the country have been facing the similar kinds of problems. During the writing, the facts were collected by inter and intrapersonal relations with the civil servants, provincial assembly members and various interaction programs with provincial stakeholders. But the core study area is Gandaki Province. The major finding of this study is that provincial cooperation and coordination is an essential factor to implementing federalism in Nepal. If the provinces failed to cooperate with federal government as well as intra-provincial government, federalism is hardly likely to sustain in Nepal.